Research on the use of algorithms for matrix transformations for encrypting text information. Issue 6 (30th March 2020) - Khanas, Yuriy; Borecki, Michał
Abstract: Several algorithms are presented in the article for the transformation of numerical matrices by nonstandard means. These algorithms are shown in the data encryption task, namely, a text message with a certain set of characters. An analysis of the effectiveness of the proposed approach will be demonstrated by comparing open source and encrypted. The algorithms developed by the author are described in as detailed and clear as possible, since they are new. At the same time, they can be difficult to reach or incorrectly interpreted by those who do not have the full amount of information about them.